2014
DOI: 10.1007/s00359-014-0935-x
|View full text |Cite
|
Sign up to set email alerts
|

Which way is up? Asymmetric spectral input along the dorsal–ventral axis influences postural responses in an amphibious annelid

Abstract: Medicinal leeches are predatory annelids that exhibit countershading and reside in aquatic environments where light levels might be variable. They also leave the water and must contend with terrestrial environments. Yet, leeches generally maintain a dorsal upward position despite lacking statocysts. Leeches respond visually to both green and near-ultraviolet (UV) light. I used LEDs to test the hypothesis that ventral, but not dorsal UV would evoke compensatory movements to orient the body. Untethered leeches w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 91 publications
3
16
0
Order By: Relevance
“…To verify that the amount of light gradually decreased from Q1 to Q4, the intensity of light in each quadrant was estimated with a phototransistor. Finally, the assay used easily-constructed LED wands powered by 9 volt batteries, as previously described [30] , [31] , which allowed for some control of the ranges of wavelengths tested. Each wand was also designed to deliver roughly equivalent numbers of photons cm −2 s −1 (flux) [30] , [31] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To verify that the amount of light gradually decreased from Q1 to Q4, the intensity of light in each quadrant was estimated with a phototransistor. Finally, the assay used easily-constructed LED wands powered by 9 volt batteries, as previously described [30] , [31] , which allowed for some control of the ranges of wavelengths tested. Each wand was also designed to deliver roughly equivalent numbers of photons cm −2 s −1 (flux) [30] , [31] .…”
Section: Resultsmentioning
confidence: 99%
“…Ambient lighting was generated by directing two 100 watt LED flashlights onto the walls on either side of an otherwise completely dark room to produce diffuse background illumination of 50–55 lux (“Light Meter–Lux Measurement Tool” Version 1.2, iPhone application). LED wands (fixed resistor and RCA plug attached to a 9 volt battery with switch) were constructed as previously described [30] , [31] . Each wand delivered roughly equivalent numbers of photons cm −2 s −1 (flux), with the following nominal wavelength ranges: near IR (700–850 nm), red (615–640 nm), green (515–520 nm), blue (460–470 nm), and 2 wavelengths of near UV (395–405 nm and 360–365 nm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an elegant follow-up study with more tightly controlled light intensities, Jellies (2014b) found that leeches also respond strongly to UV light projected onto their ventral surface, primarily by locally twisting away. Surprisingly, at the level of the central nervous system, leeches respond more strongly to UV light than to green light when ventral sensilla act as the input pathway.…”
Section: Novel Responses To Visual Stimulimentioning
confidence: 99%